2019
DOI: 10.5007/2175-7941.2019v36n3p704
|View full text |Cite
|
Sign up to set email alerts
|

A filosofia sistêmica de Fritjof Capra: Um olhar ecológico para a Física e para o Ensino de Física

Abstract: Neste artigo, apresentamos a Filosofia Sistêmica de Fritjof Capra. A partir de sua obra é possível distinguir a existência de dois paradigmas (entendidos como molduras filosóficas) no desenvolvimento da ciência moderna: o paradigma mecanicista, inspirado pela Física Clássica, e o novo paradigma, articulado a partir da Física Moderna. Segundo Capra, os problemas complexos do mundo contemporâneo podem ser mais bem enfrentados pelo novo paradigma. Para abordar o tema, apresentamos uma discussão sobre a visão de C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…A current inclination in science education is the concern with the representation of Science established by students in schools. As we may discuss in the present investigation, a common goal in the important field of teaching of Modern Physics is linked to existing misconceptions about Quantum Physics (QP), especially those related to the cultural phenomenon of quantum mysticism, that has different origins (MOURA; SANTOS, 2017; CREASE; MANN, 1982) but in our study was observed when students related Quantum to ideas of fiction criticized by some authors (HILGER: MOREIRA, 2012), or ideas spread from self-help books and related topics (PIGOZZO; LIMA; NASCIMENTO, 2019;MOURA;SANTOS, 2017).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…A current inclination in science education is the concern with the representation of Science established by students in schools. As we may discuss in the present investigation, a common goal in the important field of teaching of Modern Physics is linked to existing misconceptions about Quantum Physics (QP), especially those related to the cultural phenomenon of quantum mysticism, that has different origins (MOURA; SANTOS, 2017; CREASE; MANN, 1982) but in our study was observed when students related Quantum to ideas of fiction criticized by some authors (HILGER: MOREIRA, 2012), or ideas spread from self-help books and related topics (PIGOZZO; LIMA; NASCIMENTO, 2019;MOURA;SANTOS, 2017).…”
Section: Introductionmentioning
confidence: 62%
“…The TSR is an area of study in Social Psychology which is a branch of Psychology that seeks to study the acquisition of meanings (things, facts, concepts, ideas) by a group of individuals, mixing cognitive aspects of cognitive psychology with concepts of sociology of group collectivity. In cognitive psychology there are many theories that seek to understand how individuals treat knowledge, how they build or acquire it, some of which are the wellknown theories of Piaget (1970), Bruner (1977), Ausubel (2003) and Vergnaud (1990). However, the study of how and why individuals share knowledge, creating a common and consensual reality, putting ideas into practice are the objectives of Social Psychology (MOSCOVICI, 2015), which finds echo in the ideas of Vygotsky (2007), when proposing that learning is a process mediated by society and culture.…”
Section: Ii1 a Brief Review On The Theory Of Social Representations (...mentioning
confidence: 99%
See 1 more Smart Citation
“…As características do Pensamento Sistêmico incorporaram-se ao longo dos anos a uma maneira específica de se ver os problemas do mundo. (PIGOZZO et al, 2019). As mudanças foram gradual de ênfases, afastando a nova forma de pensar das características do método mecanicista, caracterizando um novo paradigma.…”
Section: Pensamento Sistêmicounclassified
“…O interesse por Física Quântica (FQ) e seus entrelaçamentos com assuntos como misticismo, "filosofias orientais" e medicina alternativa têm sido pautado por diversos trabalhos de pesquisa acadêmica; muitos deles devotados à análise histórica e epistemológica desse fenômeno que pode ser denominado "fenômeno cultural do misticismo quântico" (PAURA, 2018;SAITO, 2019). No Caderno Brasileiro de Ensino de Física, a título de exemplo, foram publicados dois trabalhos recentes que investigam aspectos relacionados ao fenômeno de diferentes maneiras; trabalhos a cujas discussões pretendemos dar continuidade (MOURA; SANTOS, 2017; PIGOZZO; LIMA; NASCIMENTO, 2019).…”
Section: Introductionunclassified